Perancangan E-Commerce Berbasis Website Pada Toko Mirabella Batik Jambi - Andi Ridho Rachman; Beny Beny; Erick Fernando (LPPM Universitas Dinamika Bangsa, 2017)
Mirabella Batik Jambi is a business engaged in the sale of Jambi typical batik with various types of materials such as atbm, silk, semi silk, sanwos and cotton. The system runs now where consumers still have to come directly to the store to purchase the product. Constraints faced by the store today is difficult to market or sell its products outside the city or region and can only market it in jambi region alone, the lack of new product information updates, and it affects the lack of maximum income store. The purpose of this study to design ansystem e-commerce to support the sales process that can make reservations online and provide information up todate.The method used is a method of analysis that is done by literature study, data collection (observation).Development methodmethod waterfall and emphasis UML. Types of e-commerce that is used is Business to Customer (B2C). This research resulted in anapplication e-commerce for Mirabella Batik Jambi stores to facilitate costumer to see the product in detail and make a reservation without having to come to the store simply by accessing the web site e-commerce store Mirabella Batik Jambi